Opinion 2455: Lanius leucorynchus and Psittacus mascarinus: species-group names conserved as justified emendations of punctuated original spellings, Lanius leucoryn. and Psittacus mascarin. in Linnaeus's Mantissa Plantarum Altera, 1771 - ICZN (Bulletin of Zoological Nomenclature, 2020)
The International Commission on Zoological Nomenclature has conserved the species-group names leucorynchus Linnaeus, 1771 and mascarinus Linnaeus, 1771 as respective justified emendations of the specific names for a woodswallow, Artamus leucorynchus (Linnaeus, 1771), type species of the avian genus Artamus (Artamidae), and a parrot, Mascarinus mascarinus (Linnaeus, 1771), type species of the avian genus Mascarinus (Psittacidae). Both names were originally spelled by Linnaeus (1771) in his Mantissa Plantarum Altera as “leucoryn.” and “mascarin.”, in the binomina Lanius leucoryn. and Psittacus mascarin. respectively.
Keywords: Nomenclature; taxonomy; Aves; Artamus leucorhynchus; Lanius leucoryn.; Mascarinus mascarinus; Psittacus mascarin.; Linnaeus; Mantissa Plantarum; Australasia; Indonesia; Mascarene Islands; abbreviation